Evaluasi Perencanaan Pendidikan Karakter Islam untuk Mengoptimalkan Implementasi Kurikulum : Studi Kasus di MTs Persis 23 Cirengit - Riris Sriwiguna; Mulyawan Shafwandy Nugraha (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Islamic character education has become a central focus of madrasah education; however, its planning is often implemented normatively without adequate managerial and evaluative mechanisms. This study aims to analyz ethe planning of Islamic character educationatMTs Persis 23 by examining the alignment betweent he madrasah’s strategic direction, curriculum, instructional practices, habituation programs, and character evaluation. Using a qualitative case study approach, data were collected through document analysis, classroom and school observations, and in-depth interviews with the head of the madrasah, the vice principal for curriculum, and home room teachers. Data were analyzed thematically to identify patterns of planning, implementation, and evaluation. The findings reveal that the madrasah has established a strong strategic foundation for character education through its vision, mission, and religious school culture, positioning character development as a core educational objective. Character values are integrated in to the Madrasah Operational Curriculum, lessonplans, and daily habituation activities functioning as a hidden curriculum. Nevertheless, the planning of character education remains weak at the operational level, particularly due to the absence of m easurable behavioral indicators, standar dizede valuation instruments, and systematic documentation of students’ character development. This study highlightsthe gap between normativ estrategic intentions and managerial implementation. It recommends the development of simple behavioral indicators, baselineand longitudinal character assessments, ands trengthenedpe dagogical supervision to ensure that character education planning is implemented systematically and sustainably.